An Ex vivo culture model for placental cytomegalovirus infection using slices of Guinea pig placental tissue. (January 2016) - Yamada, Souichi; Katano, Harutaka; Sato, Yuko; Fukuchi, Saki; Hashimoto, Kaede; Inoue, Naoki
Abstract: Congenital infection with human cytomegalovirus (CMV) through the placenta is one of the major causes of birth and developmental abnormalities. Guinea pig CMV (GPCMV) causes in utero infection, which makes its animal models useful for studies on congenital diseases. Here, we established an ex vivo culture method for tissue slices prepared from guinea pig placentas and demonstrated that viral spread in the model resembles those in the placenta of GPCMV-infected animals and that the infection is independent of the pentameric glycoprotein complex for endothelial/epithelial cell tropism. Thus, this model affords a useful tool for pathobiological studies on CMV placental infection. Highlights: We developed a culture model for placental infection of guinea pig cytomegalovirus. Infected cell types and the way of viral spread were similar to those in animals. Three components of the pentameric complex are dispensable for placental infection.